COVID‐19 and mucormycosis syndemic: double health threat to a collapsing healthcare system in India. Issue 9 (24th June 2021) - Rocha, Ian Christopher N.; Hasan, Mohammad Mehedi; Goyal, Samarth; Patel, Tapan; Jain, Shubhika; Ghosh, Asmita; Cedeño, Trisha Denise D.
Summary: In addition to the overwhelming and uncontrollable second wave of COVID‐19 in India, the country is also dealing with an outbreak of mucormycosis, a deadly fungal infection, which is affecting thousands of COVID‐19 patients. With the increasing number of cases of mucormycosis and a fatality rate of 50%, many Indian states and union territories have declared an epidemic of black fungus due to its unprecedented emergence, which has adversely affected the already debilitated health system of the country. The advent of the new fungal epidemic in the country is due to the overdosage, panic and injudicious use of corticosteroids among COVID‐19 patients, as well as their pre‐existing medical history of diabetes, given that India is the diabetes capital of the world. Thus, there is an urgent need to address this public health concern by having nationwide surveillance, diagnostic and management system of the disease, along with public awareness and education to combat the syndemic of COVID‐19 and mucormycosis in the country.